Integration of landscapes in healthcare facilities to heal users' body-mind health / Wi Chin Tyng and Muna Hanim Abdul Samad - Tyng, Wi Chin; Abdul Samad, Muna Hanim (Universiti Teknologi MARA, Perak, 2022)
The inclusion of nature in healthcare facilities for its restorative healing benefits began earlier in ancient times but was gradually forgotten in the development of the modern hospital. In Malaysia, it is found that most of the public hospital only focused on the built environment while disregarding the green outdoor environment. There is also a dearth of studies on the implementation of healing environment through therapeutic landscape in Malaysia. This study aims to identify the healing landscapes or therapeutic landscapes in healthcare facilities that are able to heal users’ body-mind health, and to investigate the design and construction guidelines of therapeutic gardens in Malaysian healthcare facilities. This study is conducted using the qualitative method through precedent studies and case studies on healthcare facilities integrated with landscape elements as well as the quantitative method by questionnaire survey. The study has proven that patients who spend time in the courtyard garden or therapeutic garden in healthcare facilities have shorter recovery period and experience a reduction in the level of stress and anxiety. In the future, it is also to be advised to have more studies conducted on local courtyard garden in healthcare facilities in order to fulfil the basic principle of healing garden or therapeutic garden that could heal human body-mind health.